MATERNAL AND FETAL HEALTH CHALLENGES IN HEPATITIS E-INFECTED PREGNANCIES - HUSSAIN, J; NOOR, N; REHMAN, F; ILYAS, A; TOFAIL, S (Biological and Clinical Sciences Research Journal, 2024)
The emergence of Hepatitis E virus (HEV) infection presents a mounting apprehension in less developed areas. When contracted during pregnancy, this infection instigates dire ramifications, posing grave threats to the well-being of both the expectant mother and the developing fetus. Notably, HEV accounts for a substantial fraction of maternal fatalities, encompassing a range of 19% to 25%, while also contributing to a noteworthy 7-13% of neonatal deaths. The primary objective of this study is to delve into the intricate relationship between HEV infection and the ensuing consequences for maternal and fetal health during pregnancy. Objectives: To explore the e maternal and fetal outcomes in pregnant women with Hepatitis E. Methods: A prospective study design was implemented, and 160 pregnant women were enrolled. The study was conducted at a tertiary healthcare facility over the period spanning from April 2021 to September 2022 after fulfilling the inclusion criteria and consent form. The collected data were entered and analyzed by using SPSS version 23. Results: A total of 160 pregnant women enrolled in this study, the mean age 30.90±7.323 (Age Range 18-44); gestational age was divided into two groups ≥ 36 weeks 77(48.1%) compared with ≥ 36 weeks as 83(51.9%).The frequency distribution of table -2 showed postpartum hemorrhage 82(51.2%), disseminated intravascular coagulation 70(43.8%) and hepatic encephalopathy 46(28.8%). The mode of pregnancy termination due to hepatitis E virus infection showed induction of labor 64(40%), hysterectomy 111(69.4%), and dilation and evacuation (D&E) 84(52.5%). While comparing maternal HEV infection with other research variables, it was observed that there was a significant difference found in HEV-positive pregnant women and low birth weight (< 2500g), fetal scalp monitors during delivery, and hysterectomy as p-value < 0.05. Conclusion: A high mortality rate was evident in hepatitis E virus infection-affected pregnancies in this study. There is a need to educate pregnant ladies regarding preventive measures to avoid fulminant consequences. Emphasis should be given to following hygienic practices during pregnancy, and proper antenatal visits should be mandatory to educate the women.